2014
DOI: 10.1371/journal.pone.0086763
|View full text |Cite
|
Sign up to set email alerts
|

The Iron-Sulphur Cluster Biosynthesis Regulator IscR Contributes to Iron Homeostasis and Resistance to Oxidants in Pseudomonas aeruginosa

Abstract: IscR is a global transcription regulator responsible for governing various physiological processes during growth and stress responses. The IscR-mediated regulation of the Pseudomonas aeruginosa isc operon, which is involved in iron-sulphur cluster ([Fe-S]) biogenesis, was analysed. The expression of iscR was highly induced through the exposure of the bacteria to various oxidants, such as peroxides, redox-cycling drugs, intracellular iron-chelating agents, and high salts. Two putative type 1 IscR-binding sites … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
77
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 46 publications
(81 citation statements)
references
References 33 publications
3
77
0
Order By: Relevance
“…While activation of the siderophore pyochelin could be hypothesized to be a result of the recognition of iron limitation by P. aeruginosa , the overall gene expression pattern did not confirm this. Except for pyochelin, none of the other iron limitation-induced genes, however the iron-sulphur [Fe-S] cluster assembly genes (PA3812-PA3814, iscA , iscU , iscS ) (17) was up-regulated in our study (Fig.5C, supplemental table S1) possibly to reduce the total intracellular iron content increased due to pyochelin action. Genes encoding multidrug efflux pump MexGHI-OpmD (PA4207 mexI , PA4208 opmD ) were also activated.…”
Section: Resultsmentioning
confidence: 55%
“…While activation of the siderophore pyochelin could be hypothesized to be a result of the recognition of iron limitation by P. aeruginosa , the overall gene expression pattern did not confirm this. Except for pyochelin, none of the other iron limitation-induced genes, however the iron-sulphur [Fe-S] cluster assembly genes (PA3812-PA3814, iscA , iscU , iscS ) (17) was up-regulated in our study (Fig.5C, supplemental table S1) possibly to reduce the total intracellular iron content increased due to pyochelin action. Genes encoding multidrug efflux pump MexGHI-OpmD (PA4207 mexI , PA4208 opmD ) were also activated.…”
Section: Resultsmentioning
confidence: 55%
“…In E. coli , the expression of the isc genes is repressed by the IscR transcriptional regulator in response to high levels of these clusters (Schwartz et al ., ), as well as by the iron‐responsive sRNA rhyB (Desnoyers et al ., ). Interestingly, the increased expression of IscR in P. aeruginosa carrying a multicopy plasmid with iscR increases the total iron content of the cells and reduces siderophore production (Romsang et al ., ). In the present work, the mRNA levels of iscR (PP_0841) in the P. putida Hfq/Crc‐null strain were more than five‐fold higher than in the wild type strain (Supporting Information Table S3).…”
Section: Resultsmentioning
confidence: 97%
“…4A). High level of promoter sequence conservation is found among Gram-negative bacteria, particularly pathogenic bacteria for which a number of putative IscR binding sites were recently identified [9,12,48].…”
Section: Iscr: One Dna-binding Domain Two Dna-binding Motifsmentioning
confidence: 99%
“…P. aeruginosa iscR mutant was shown to be hypersensitive to H 2 O 2 and paraquat, due to decreased catalase A (KatA) enzyme activity [73]. More recently, it was shown that IscR regulated the P. aeruginosa isc operon under both physiological and stress conditions, conferring resistance to oxidative stress and contributing to iron homeostasis [48]. In Shigella flexneri, a facultative intracellular pathogen and the causative agent of bacterial dysentery, the expression of both suf and isc promoters increased when the pathogen was living intracellularly due to iron scarcity.…”
Section: Implications Of Iscr In Host-pathogen Interactionsmentioning
confidence: 99%